A Santa montanha : conteúdos messiânicos de um movimento sócio-religioso (1999-2003) - Feital, Frederico André Gonçalves (2008)
It treats as the analysis of the contents messiânicos of a movement religious partner who happens in Villas-Boas, local authority of Guiricema, Zone of the Forest of Minas Gerais: The Holy Mountain. The Holy Mountain appears at a critical moment for the civil Brazilian society, 1966, time dominated by the militarism. From the apparition of Our Lady, a humble farm-hand starts to coordinate a complex social movement that includes 3000 persons at his moments of communion. The theoretical used referential system is based on Eric Hobsbawm and Maria Isaura Pereira of Queiroz, for whom the religious rural movements are political movements, in so much in what they represent aspirations and social interests in front of the State and what the behaviour of the leaders – prophets or messengers – and of his disciples they are mechanisms of political and cultural resistance. To the end partner-monk tries to establish vinculação between the facts been present in the Holy Mountain and other movements.